2018
DOI: 10.1111/head.13298
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Method of Action of Intravenous Lidocaine and Its Metabolite in Headache Disorders

Abstract: Open label and retrospective studies have investigated the use of lidocaine in many headache disorders, primarily via injection or infusion. Further research into the active metabolite of lidocaine may allow for its use as a novel nonopiate treatment of chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 53 publications
0
14
0
4
Order By: Relevance
“…The analgesic benefits of lidocaine also may be mediated indirectly via its primary metabolite, monoethylglycine (MEG) [ 24 , 26 ]. Animal models suggest that MEG attenuates the inflammatory pain response and indirectly regulates the extracellular glycine concentration via competitive inhibition of the glycine transporter, GlyT1 [ 26 ]. Glycine is a major neurotransmitter involved in the descending regulation of pain [ 25 , 26 ].…”
Section: Intravenous Lidocainementioning
confidence: 99%
“…The analgesic benefits of lidocaine also may be mediated indirectly via its primary metabolite, monoethylglycine (MEG) [ 24 , 26 ]. Animal models suggest that MEG attenuates the inflammatory pain response and indirectly regulates the extracellular glycine concentration via competitive inhibition of the glycine transporter, GlyT1 [ 26 ]. Glycine is a major neurotransmitter involved in the descending regulation of pain [ 25 , 26 ].…”
Section: Intravenous Lidocainementioning
confidence: 99%
“…Lidocaine is a local anesthetic that exerts efficacy within 1–3 min after administration, with an anesthetic effect that lasts for 1–3 h ( 6 ). In clinical practice, it is used to treat arrhythmia and is the first line of treatment for patients with ventricular tachycardia and tremor ( 7 , 8 ). The current evidence has demonstrated that treatment with lidocaine eliminates severe arrhythmia and prevents heart death in an in vivo rat model of acute myocardial I/R ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides local anesthesia, lidocaine is capable for general anesthesia, intrathecal anesthesia, and antiarrhythmic as well. 12 , 13 In 1961, Bartlett and Hutaserani had firstly shown the efficacy of systemic lidocaine for the relief of postoperative pain. 14 Recent studies have given credit for the strategy that bolus infusion of lidocaine 1~1.5 mg/kg during anesthesia induction followed by a continuous infusion of lidocaine 1.5~2 mg/kg/h until the end of surgery.…”
Section: Introductionmentioning
confidence: 99%